2013
DOI: 10.1101/gad.213827.113
|View full text |Cite
|
Sign up to set email alerts
|

A RANKL–PKCβ–TFEB signaling cascade is necessary for lysosomal biogenesis in osteoclasts

Abstract: Bone resorption by osteoclasts requires a large number of lysosomes that release proteases in the resorption lacuna. Whether lysosomal biogenesis is a consequence of the action of transcriptional regulators of osteoclast differentiation or is under the control of a different and specific transcriptional pathway remains unknown. We show here, through cell-based assays and cell-specific gene deletion experiments in mice, that the osteoclast differentiation factor RANKL promotes lysosomal biogenesis once osteocla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
163
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(167 citation statements)
references
References 59 publications
4
163
0
Order By: Relevance
“…Semi-quantitative RT-PCR was carried out as described earlier (28) using oligo(dT) [12][13][14][15][16][17][18] as primer and Moloney murine leukemia virus-RT in a 20-l reaction mixture. The resulting cDNA was appropriately amplified using Promega Master Mix (Madison, WI) and the following primers (Life Technologies) for murine genes: mouse Tfeb, sense, 5Ј-AAC AAA GGC ACC ATC CTC AA-3Ј, and antisense, 5Ј-CAG CTC GGC CAT ATT CAC AC-3Ј; mouse Lamp2, sense, 5Ј-GGT GCT GGT CTT TCA GGC TTG ATT-3Ј, and antisense, 5Ј-ACC ACC CAA TCT AAG AGC AGG ACT-3Ј; mouse Limp2, sense, 5Ј-TGT TGA AAC GGG AGA CAT CA-3Ј, and antisense, 5Ј-TGG TGA CAA CCA AAG TCG TG-3Ј; mouse Npc1, sense, 5Ј-GGG ATG CCC GTG CCT GCA AT-3Ј, and antisense, 5Ј-CTG GCA GCT ACA TGG CCC CG-3Ј; mouse Gapdh, sense, 5Ј-GCA CAG TCA AGG CCG AGA AT-3Ј, and antisense, 5Ј-GCC TTC TCC ATG GTG GTG AA-3Ј. Amplified products were electrophoresed on 2% agarose gels and visualized by ethidium bromide staining.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-quantitative RT-PCR was carried out as described earlier (28) using oligo(dT) [12][13][14][15][16][17][18] as primer and Moloney murine leukemia virus-RT in a 20-l reaction mixture. The resulting cDNA was appropriately amplified using Promega Master Mix (Madison, WI) and the following primers (Life Technologies) for murine genes: mouse Tfeb, sense, 5Ј-AAC AAA GGC ACC ATC CTC AA-3Ј, and antisense, 5Ј-CAG CTC GGC CAT ATT CAC AC-3Ј; mouse Lamp2, sense, 5Ј-GGT GCT GGT CTT TCA GGC TTG ATT-3Ј, and antisense, 5Ј-ACC ACC CAA TCT AAG AGC AGG ACT-3Ј; mouse Limp2, sense, 5Ј-TGT TGA AAC GGG AGA CAT CA-3Ј, and antisense, 5Ј-TGG TGA CAA CCA AAG TCG TG-3Ј; mouse Npc1, sense, 5Ј-GGG ATG CCC GTG CCT GCA AT-3Ј, and antisense, 5Ј-CTG GCA GCT ACA TGG CCC CG-3Ј; mouse Gapdh, sense, 5Ј-GCA CAG TCA AGG CCG AGA AT-3Ј, and antisense, 5Ј-GCC TTC TCC ATG GTG GTG AA-3Ј. Amplified products were electrophoresed on 2% agarose gels and visualized by ethidium bromide staining.…”
Section: Methodsmentioning
confidence: 99%
“…The regulation of Tfeb appears to be complex and dependent on cell type and stimuli. In differentiated osteoclasts, a receptor activator of NF-B ligand-dependent signaling pathway induces TFEB activation and lysosomal biogenesis (13). Starvation or stress conditions may also activate TFEB, which otherwise is maintained in an inactivated state by mTORC1 (14,15).…”
mentioning
confidence: 99%
“…The lysosomal biogenesis dysfunction observed in Tfeb −/− osteoclasts is probably caused by a direct effect on lysosomal gene transcription, since TFEB binds the promoter region of several lysosomal genes (Atp6v1c1, Clcn7, and Ctsk), and loss of Tfeb in osteoclasts is characterized by lower expression levels of Acp5, Atp6v1c1, Clcn7, Ctsk, and Tcirg1. 86 Altogether, these data point to TFEB as a critical regulator of lysosomal biogenesis directly modulating the expression of key effectors in this process.…”
Section: Transcriptional Control Of Lysosomal Biogenesis In Osteoclastmentioning
confidence: 99%
“…Importantly, this occurs without affecting osteoclasts number. 86 The dissociation of the role of RANKL in osteoclasts differentiation from the one it has in lysosomal biogenesis suggested that RANKL might control osteoclasts differentiation and activity through distinct mechanisms.…”
Section: Transcriptional Control Of Lysosomal Biogenesis In Osteoclastmentioning
confidence: 99%
See 1 more Smart Citation